Exploring Quantum-Confinement Effects in Two-Dimensional Materials Synthesized via Chemical Vapor Deposition for Next-Generation Optoelectronic Devices - Shehroz Abdullah ,; Saddam Hussain,; Madiha Liaquat, (Dialogue Social Science Review (DSSR), 2025)
This work aims to understand the impact of quantum confinement in CVD grown 2D materials with an interest in futuristic optoelectronic gadgets. Quantum confinement, which takes place when the material thickness is reduced to monolayers or few-layer film, leads to changes in the electronic, optical, mechanical properties as well as boosting photoluminescence, band gap and carrier mobility. In this context materials such as graphene, molybdenum disulfide (MoS2​), black phosphorus etc. are being reasoned. Brand and his coworkers used the CVD technique to grow monolayer and few-layer 2D materials with well-controlled thickness, morphology and crystallinity. These studies also reveal that monolayer MoS2_22​ and black phosphorus are predicted to have direct band gaps, strong photoluminescence, and high exciton binding energies that are well-suited for optoelectronics applications including photodetectors, light-emitting diodes and solar cells. Optoelectronic application of graphene, which does not possess a fundamental band gap, can be derived from quantum confinement effects which may include doping or lateral size control. In summary, the study supports the notion that the phenomena of quantum confinement in 2D materials holds potential for the construction of highly efficient, large-scale optoelectronic arrays. These observations emphasize the role of CVD synthesis in the preparation of defect free monolayers applicable to large area device fabrication.